Bioinspired Polymer Nanocomposites Exhibit Giant Energy Density and High Efficiency at High Temperature. Issue 28 (14th May 2019) - Xu, Wenhan; Liu, Jie; Chen, Tianwu; Jiang, Xiangyu; Qian, Xiaoshi; Zhang, Yu; Jiang, Zhenhua; Zhang, Yunhe
Abstract: Polymer dielectrics are ubiquitous in advanced electric energy storage systems. However, the relatively low operating temperature significantly menaces their widespread application at high temperatures, such as for hybrid vehicles and aerospace power electronics. Spider silk, a natural nanocomposite comprised of biopolymer chains and crystal protein nanosheets combined by multiple interfacial interactions, exhibits excellent mechanical properties even at elevated temperatures. Inspired by the hierarchical nanostructure of spider silk, poly(aryl ether sulfone) is anchored to the surface of wide bandgap artificial nanosheets to prepare the nanocomposites with nanoconfinement effect. The bioinspired strategy successfully improves the mechanical and electrical performances of the nanocomposite. Owing to the structural‐enabled enhancements, the nanocomposites exhibit excellent breakdown strength and electrical energy storage performance at high temperatures. In detail, giant discharged energy density (2.7 J cm −3 ) and high charge–discharge efficiency (>90%) are simultaneously achieved at 150 °C and 400 MV m −1 . Notably, under 500 MV m −1, the discharged energy density reaches 4.2 J cm −3, which is the record high discharged energy density among polymer‐based dielectrics at 150 °C. This work demonstrates a viable strategy to design high‐temperature polymer dielectrics by constructing nanoconfinement in the nanocomposites. Abstract : Bioinspired polymer nanocomposites achieved by nanoconfinement exhibit giant energy density and high efficiency. The nanoconfinement via multiple chemical bonds between fillers and polymer matrix significantly enhance the nanocomposite electric energy storage properties at high temperature. This work may promote wider applications of polymer dielectrics in elevated temperatures.